Comparison of the effects of direct laryngoscopic and fiberoptic oral endotracheal intubation on the intraocular pressures of non-ophthalmic patients: A prospective, randomised, clinical trial (Annals of Medical Research, 2022)
Aim: In this prospective, randomised, clinical study; we aimed to compare the effects of endotracheal intubation (ETI) via direct laryngoscope (DLS) and fiberoptic bronchoscope (FOB) on intraocular pressure (IOP)  and hemodynamic data of non-ophthalmic patients.Materials and Methods: Fifty-four adult patients undergoing non-ophthalmic surgeries performed in the supine position under general anesthesia requiring orotracheal intubation were included into the study. The patients were randomly and prospectively divided into 2 groups: Group DLS (n=27) and Group FOB (n=27). Mean arterial pressure (MAP), Heart rate (HR), IOP were measured at before induction (basal), post-induction and 1st, 2nd, 3rd, and 5th minutes of intubation.Results: There was no statistically significant difference in distribution of patient characteristics. Duration of intubation was significantly longer in Group FOB (p
Keywords: Direct laryngoscope; Fiberoptic bronchoscope; Intraocular pressure; Hemodynamics